2018
DOI: 10.1016/j.dcn.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental variation in regional brain iron and its relation to cognitive functions in childhood

Abstract: Non-heme iron is a vital metabolic cofactor for many core processes of brain development including myelination, dendritogenesis, and neurotransmitter synthesis, and accumulates in the brain with age. However, little is known about development-related differences in brain iron and its association with emerging cognitive abilities during formative years. In this study, we estimated brain iron via R2* relaxometry in children ages 7–16 (N = 57; 38 females) and examined its relation to age-related differences in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 79 publications
6
26
0
2
Order By: Relevance
“…We used a multimodal neuroimaging approach to investigate developmental changes in indices of pre-and post-synaptic DA neurobiology through adolescence and young-adulthood. R2′ measures of tissue iron concentration showed increases throughout adolescence, replicating prior work 23,24,29,31,32 and were specifically associated with PET DTBZ measures of presynaptic vesicular dopamine. Given that DTBZ BP quantifies presynaptic vesicular DA storage 30 , these findings suggest that DA availability, following the observed developmental pattern of R2′, increases through the adolescent period before stabilizing by early-adulthood.…”
Section: Discussionsupporting
confidence: 80%
“…We used a multimodal neuroimaging approach to investigate developmental changes in indices of pre-and post-synaptic DA neurobiology through adolescence and young-adulthood. R2′ measures of tissue iron concentration showed increases throughout adolescence, replicating prior work 23,24,29,31,32 and were specifically associated with PET DTBZ measures of presynaptic vesicular dopamine. Given that DTBZ BP quantifies presynaptic vesicular DA storage 30 , these findings suggest that DA availability, following the observed developmental pattern of R2′, increases through the adolescent period before stabilizing by early-adulthood.…”
Section: Discussionsupporting
confidence: 80%
“…Model estimated regional R2* values-covarying for sex and visit number-closely matched prior studies (Hallgren and Sourander, 1958;Bartzokis et al, 1997Bartzokis et al, , 2007Aquino et al, 2009;Péran et al, 2009;Haacke et al, 2010 p.201;Langkammer et al, 2010;Sedlacik et al, 2014;Ghadery et al, 2015;Hect et al, 2018 3). All regions significantly differed from each other (Table 2).…”
Section: Regional Differences In Iron Concentrationsupporting
confidence: 52%
“…All studies included in this review controlled for sex during their analyses. Fifteen of the included studies assessed sex-mediated brain iron differences statistically; 1 study found that while temporal iron levels did not significantly differ between men and women, cerebellar iron was significantly higher in males compared to females [ 27 ]; 1 studies found significantly higher hippocampal iron in men compared to women [ 28 ]; 1 study found that regional brain iron in women plateaus later than in men during development [ 1 ] and the remaining 12 studies observed no significant difference in brain iron in any assessed region between males and females [ 29 , 31 , 34 – 36 , 38 , 42 , 44 , 47 , 51 , 54 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haller et al, 2010 [43] There was a significantly increased iron concentration in R-PA and R-SN in MCI groups compared to controls (p<0.01); There was significantly decreased iron concentration in the R-RN in MCI groups compared to controls (p<0.05); No difference in iron concentration was found in any regions between stable and progressive MCI Hect et al, 2018 [44] Brain iron in CN (p = 0.03), PU (p<0.01), GP (p = 0.04) and SN (p<0.01) correlated with general intelligence scores; Brain iron in the CN (p<0.001) and PU (p<0.01) correlated processing speed; HP (p>0.69) and RN (p>0.33) iron content were unrelated to cognition; Greater general brain iron content predicted faster processing speed (p = 0.02) and better general intelligence (p = 0.01)…”
Section: Ghadery Et Al 2015 [42]mentioning
confidence: 99%